Modern approach to implementation of health related technology for primary school children - L.V. Shuba (H.S. Skovoroda Kharkov National Pedagogical University, 2016)
Purpose: to work out and experimentally prove health related technology, which would facilitate formation of pupils' healthy life style. Material: In the research pupils of 8-9 years' age participated. From four tested forms we composed four groups. Control groups consisted of 19 boys and 17 girls; experimental groups - of 20 boys and 16 girls, who were practically healthy. Results: the highest absolute increment of physical fitness indicators in experimental group was found in such motor abilities as flexibility, strength of hands' and torso muscles, speed-power qualities. It was noted that for effective development of pupils' physical qualities decisive factor was consideration of sensitive periods and complex approach at physical culture classes. Conclusions: the received results witness about effectiveness of the worked out by us technology. It consists of two blocks with prevailing usage of health related exercises.